2021
DOI: 10.4081/ripppo.2021.517
|View full text |Cite
|
Sign up to set email alerts
|

Italia Ti Ascolto [Italy, I am listening]: an app-based group psychological intervention during the COVID-19 pandemic

Abstract: The onset of the coronavirus disease 2019 (COVID-19) pandemic impacted individuals’ psychological wellbeing resulting in heightened perceived stress, anxiety, and depression. However, a significant issue in accessing psychological care during a lockdown is the lack of access to in-person interventions. In this regard, research has shown the efficacy and utility of psychological app-based interventions. ‘Italia Ti Ascolto’ (ITA) has been developed as a population tailored internet-based intervention to offer an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Moreover, as recent years have witnessed a significant increase in the implementation of effective online versions of psychological interventions [ 48 , 49 ], emphasizing the opportunity for more agile and easier dissemination of evidence-based protocols, the online version of the intervention (eCONNECT) was designed and tested within the context of the pandemic period [ 50 , 51 ]. However, no data are available for this program in regard to the Italian population.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as recent years have witnessed a significant increase in the implementation of effective online versions of psychological interventions [ 48 , 49 ], emphasizing the opportunity for more agile and easier dissemination of evidence-based protocols, the online version of the intervention (eCONNECT) was designed and tested within the context of the pandemic period [ 50 , 51 ]. However, no data are available for this program in regard to the Italian population.…”
Section: Introductionmentioning
confidence: 99%
“…Nine of these studies were conducted in the period between March 2020 to May 2020, which corresponds to the introduction of nationwide restrictive measures (in many cases a lockdown) between March 9 and March 23 across the countries studied in this scoping review. Among the remaining two studies, one intersected with another period of lockdown in Italy [25], and the other immediately followed the loosening of restrictions in Denmark [26]. The timelines and pertinent restrictive measures for each study are summarised in Figure 2.
Figure 2. Graphic highlighting the timeline of studies eligible for this scoping review and associated restrictive measures by country.
…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to highlight, that this study was not conceptualized to assess the efficacy of a self-guided e-mental health intervention. One different study provides an overview of the intervention protocol of an app-based psychological group intervention as well as preliminary baseline data ( 37 ). One study applying qualitative research methods showed overall good acceptance of telehealth to foster mental health.…”
Section: Introductionmentioning
confidence: 99%